2019
DOI: 10.1016/j.ygyno.2019.04.680
|View full text |Cite
|
Sign up to set email alerts
|

HPV-prevalence in elderly women in Denmark

Abstract: Aim. In countries like Denmark, cervical cancer incidence is at present relatively high in elderly women, while routine screening stops at age 65 years. On this background, all women aged 69 and above were invited to human papillomavirus (HPV)-screening in Denmark in 2017.Methods. Women were identified from the Central Population Register and personally invited by digital or ordinary mail to have a screening sample taken by their general practitioner. In four regions, samples were tested for high risk (HPV) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 16 publications
1
36
1
Order By: Relevance
“…Another limitation is that women aged 60-64 at baseline Original research were neither routinely invited again for screening nor covered by the one-time screening offer. 23 We found an overall HPV prevalence at baseline of 8.0%, which was highest (10.7%) among the youngest women (50-54 years) and lowest (5.8%) among the oldest women (65+). The figures for the youngest women were slightly higher than those reported in another Danish study of similar age groups from another area (Capital Region of Denmark) a few years' earlier (2002)(2003)(2004)(2005)).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Another limitation is that women aged 60-64 at baseline Original research were neither routinely invited again for screening nor covered by the one-time screening offer. 23 We found an overall HPV prevalence at baseline of 8.0%, which was highest (10.7%) among the youngest women (50-54 years) and lowest (5.8%) among the oldest women (65+). The figures for the youngest women were slightly higher than those reported in another Danish study of similar age groups from another area (Capital Region of Denmark) a few years' earlier (2002)(2003)(2004)(2005)).…”
Section: Discussionmentioning
confidence: 65%
“…Among women aged 65+ at baseline, follow-up was 68.1%, which is probably explained by the one-time offer of an HPV test in 2017 to all women born before 1948 (being 69+ in 2017). 23 Finally, the usefulness of the study and the results in Danish and other settings is underlined by the fact that Cobas 4800 and liquid-based cytology, are still among the most used tests in laboratories around the world.…”
Section: Discussionmentioning
confidence: 99%
“…HPV-based screening is offered to women aged 60-64 years; and in 2017, the Danish Health Authorities invited women born before 1948 for a onetime HPV-based screening offer. 11 Patients with abnormal cytology or a positive HPV test are referred for colposcopy and cervical biopsy at a gynaecological outpatient clinic or at a private gynaecologist.…”
Section: Materials and Methods Settingmentioning
confidence: 99%
“…All HPV testing will be performed using the clinically validated and Federal Drug Agency-approved Cobas 4800 DNA test (Roche Diagnostics, Switzerland), 45 as this is the routine test platform used in the CDR. The test is an automated real-time PCR-based test designed to detect high-risk HPV types: 16,18,31,33,35,39,45,51,52,56,58,59, 66 and 68 45 46 and is validated for use on SurePath collected samples. 47 Results will be reported as (1) HPV negative, (2) HPV positive (HPV16, HPV18 and/ or other HPV types) or (3) invalid.…”
Section: Self-sampling Kitmentioning
confidence: 99%
“…[14][15][16][17] However, a recent Danish study of HPV DNA prevalence in women aged 69 and above showed no increase in prevalence that could explain the cervical cancer peak at older ages. 18 The authors stated that this result may be explained by the fact that an HPV infection may become undetectable at a late stage in the oncogenic process. 18 19 It has also been hypothesised that the current peak in older ages could be attributed to an insufficient screening history in older birth cohorts.…”
mentioning
confidence: 99%